Comparison of Enterprise Risk Management Practices in Listed and Non-listed Companies: Evidence from Croatia - Ivana DVORSKI LACKOVIC; Danijela MILOS SPRCIC (Communications of International Proceedings, 2021)
The COVID-19 pandemics has raised attention to the importance of managing risks companies are exposed to adequately. Enterprise Risk Management (ERM) is a contemporary strategic approach to risk management, aimed at achieving strategic goals, increasing shareholder value and corporate resilience. Some of the basic practices that arise from ERM definition are establishment of clear responsibility for the process, estimating all types of risks companies are exposed to and using variety of appropriate risk identification and assessment techniques. Majority of former ERM research has been focused on exploring listed companies. In this paper we wish to enrich the existing body of knowledge by increasing the sample of research with non-listed companies and comparing ERM practices in them. The results of the research, based in descriptive statistics, have served as a basis for formulation of suggestions for future scientific research, but also for practical guidelines for companies related to implementation of ERM practices.
Keywords: Enterprise Risk Management; Chief Risk Officer; risk department; risk types; risk management techniques